2017
DOI: 10.1253/circj.cj-16-1316
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Transcutaneous Oximetry of the Buttocks ― External Validation With Computed Tomography Angiography ―

Abstract: Background: Exercise transcutaneous oximetry (Ex-tcPO2) is a non-invasive test for exercise-induced buttock ischemia. Prior study defined Ex-tcPO2 normal/abnormal cut-offs against arteriography but no external validation was available. The aims of this study were therefore to (1) determine the diagnostic performance of Ex-tcPO2 against CTA; (2) determine the cut-off point for detection of stenosis >75% in arteries toward the hypogastric circulation; and (3) determine the effect of chest profile classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…This standardized methodology associated with the use of the delta from rest of oxygen pressure (DROP) cut-off has improved the reliability of this procedure that was confirmed by two studies 17,18 . Finally, two different teams found similar cut-off values of the DROP 8,10,12,19 8 .…”
mentioning
confidence: 71%
“…This standardized methodology associated with the use of the delta from rest of oxygen pressure (DROP) cut-off has improved the reliability of this procedure that was confirmed by two studies 17,18 . Finally, two different teams found similar cut-off values of the DROP 8,10,12,19 8 .…”
mentioning
confidence: 71%
“…A minimal DROP value (DROP min ) under – 15 mmHg is considered as indicating regional blood flow impairment. It has been validated as a sensitive and specific indicator for arterial lesions, in a population with proximal or distal claudication (Abraham et al, 2003, 2005; Audonnet et al, 2017). From October 2018, all the patients (whatever their usual speed and time required to walk 10 m in the corridor) had a standard treadmill protocol that included a 1‐min progressive increase in speed and slope to 3.2 km/hr and 10%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, some patients are slow walkers and are likely unable to walk for at least one minute at the standard speed and slope. This has led us since 2003 and until September 2018, to submit patients unable to walk 10 m within 12 s, to a slow speed protocol (2.0 km/hr, 10% slope) although no proof was available that the results of this slow speed protocol were the same as those of a normal standard procedure (Audonnet et al, 2017; Mahe et al, 2010). This was based on the hypothesis that a very brief walking period could be too short to allow ischaemia to occur and might result in a high rate of false‐negative tests at a standard speed compared to a slower speed but longer period of walking.…”
Section: Introductionmentioning
confidence: 99%
“…11, 12 We defined normal limits to be used and validated the technique against gold-standard arteriography at the calf and buttock level, 11,12 or computed tomography angiography. 13 We showed that Ex-tcPO2 also accounts for eventual systemic arterial oxygen pressure changes through the use of the chest electrode. 14 Since 2000 we have progressively integrated Ex-tcPO2 in our diagnostic routine of claudication as a tool to argue for the vascular origin of exercise-induced pain, specifically at the proximal level.…”
mentioning
confidence: 89%